Urban-population density patterns and change in ireland, 1901-1979 - Hourihan, K (Economic & Social Studies, 1982)
Precis: There were major changes in the population geography of the three largest cities in the Republic of Ireland during the twentieth century. Population densities in inner city areas have declined rapidly and most growth has been in suburban developments on the peripheries of the cities. Clark's (1951) negative exponential curve provides a very good fit to the population densities at each census year, and the changing patterns are summarised by the parameters of the model. Dublin especially has changed very quickly although its density was not particularly low by international standards about 1970. There are a number of problems associated with the present density patterns and these deserve urgent consideration.
Keywords: Economics; Sociology